2001
DOI: 10.1081/ja-100102640
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Among Noninjecting Drug Users: A Report

Abstract: Our results suggest that more research is needed to elucidate potential noninjecting routes of HCV transmission among drug users. Moreover, policies that rely predominantly on injector status as the only drug-related risk factor for HCV screening need to be reassessed in light of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 17 publications
2
63
2
Order By: Relevance
“…We found 28 published reports that met our criteria (Allwright et al, 2000;Baozhang et al, 1997;Broers et al, 1998;Chang et al, 1999;Denis et al, 2000;Feldman et al, 2000;Fuller et al, 2004;Galperim et al, 2004;Garten et al, 2004;Gyarmathy et al, 2002;Harsch et al, 2000;Hershow et al, 1998;Howe et al, 2005;Koblin et al, 2003;Lai et al, 2001;Maayan et al, 1994;Mathei et al, 2005;Njoh et al, 1997;Nyamathi et al, 2002;Quaglio et al 2003a;Quaglio et al 2003b;Santana Rodriguez et al, 1998;Shrestha et al, 1998;Strasfeld et al, 2003;Tortu et al, 2001;Tortu et al, 2004;Van Ameijden et al, 1993;Ward et al, 2000). One report included two separate studies, both of which were included (Tortu et al, 2001) and which appear in Table 1 in two separate rows; two reports were by the same author and indicated the same overall seroprevalence and sample size, therefore we counted this as one study (Quaglio et al 2003a(Quaglio et al & 2003b.…”
Section: Study Characteristicsmentioning
confidence: 85%
See 3 more Smart Citations
“…We found 28 published reports that met our criteria (Allwright et al, 2000;Baozhang et al, 1997;Broers et al, 1998;Chang et al, 1999;Denis et al, 2000;Feldman et al, 2000;Fuller et al, 2004;Galperim et al, 2004;Garten et al, 2004;Gyarmathy et al, 2002;Harsch et al, 2000;Hershow et al, 1998;Howe et al, 2005;Koblin et al, 2003;Lai et al, 2001;Maayan et al, 1994;Mathei et al, 2005;Njoh et al, 1997;Nyamathi et al, 2002;Quaglio et al 2003a;Quaglio et al 2003b;Santana Rodriguez et al, 1998;Shrestha et al, 1998;Strasfeld et al, 2003;Tortu et al, 2001;Tortu et al, 2004;Van Ameijden et al, 1993;Ward et al, 2000). One report included two separate studies, both of which were included (Tortu et al, 2001) and which appear in Table 1 in two separate rows; two reports were by the same author and indicated the same overall seroprevalence and sample size, therefore we counted this as one study (Quaglio et al 2003a(Quaglio et al & 2003b.…”
Section: Study Characteristicsmentioning
confidence: 85%
“…There was overlap between study samples in some cases, (Tortu et al, 2001;Tortu et al, 2004) and (Fuller et al, 2004;Howe et al, 2005;Koblin et al, 2003). For calculations of median HCV prevalence, we used the study with the largest NIDU sample (Howe et al, 2005;Tortu et al, 2001) and chose not to include the three others (Fuller et al, 2004;Koblin et al, 2003;Tortu et al, 2004) in order to avoid double counting overlapping samples.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5% in Limburg. Other studies targeting populations of non-IDU have reported prevalence rates widely varying between 2 and 25 % [4,[11][12][13][14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%